Investigation of corruption prevention plan in construction industries - Aditya Arie Hetami; Muhammad Fikry Aransyah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The business construction in Indonesia is subject to widespread corruption. The efficiency of business construction operations is constrained by corrupt judiciaries, which complicate the resolution process and weaken the protection of property rights. Construction industry corruption undermines the results of Indonesia's construction project and construction industry. The purpose of this paper is to provide an overview of corruption in construction activities so that stakeholders have exposure and discuss the prevention plan of corruption practices. A complete literature review identified a total of 10 preventive corruption practices in the construction industry were (1) enforcement of the law, regulation, and sanction; (2) high integrity and honest construction culture; (3) active reporting channel; (4) audit mechanism; (5) code of conduct; (6) public disclosure; (7) whistle-blowers protection; (8) Comprehensive supervision; (9) appropriate training program; and (10) income level adequacy. This paper seeks to thoroughly investigate an effective preventive plan in corruption practices, especially the construction sector. It provides insight and increases awareness of corruption practices among the construction stakeholders and society